Greta says that the expression (2xa)+5 is the same as 2x(a+5). Is she correct?

### 1 Answer | Add Yours

Hi, Brooke,

Since "a" is what's called "a variable", it can represent any number you want. "You have the power". So, just literally picking anything, let's say a=3. So, we would have:

**(2x3)+5 and 2x(3+5)**

Now, we always do what's in parenthesis first. So, for the left expression, we do 2x3 first. 2x3 = 6. Then, adding 5, 6+5 = 11. So, we have:

**(2x3)+5 = 11 and 2x(3+5)**

We just haven't done the right one yet. Now, we do that one. Always parenthesis first. So, 3+5 = 8. Then, we multiply that by the 2 at the beginning. 2x(8) = 16. So, we have:

**(2x3)+5 = 11 and 2x(3+5)=16**

So, Brooke, since 11 and 16 are different and not the same, then (2xa)+5 and 2x(a+5) can't be the same.

I hope this assist, Brooke. Good luck.

Steve

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes